STUDI TENTANG BUDAYA KERJA APARATUR KECAMATAN SAMBOJA, KABUPATEN KUTAI KARTANEGARA - Amir Lufni (Jurnal Paradigma (JP), 2017)
This study aims to describe apparatus’s work culture of Kutai Kartanegara particularly in Samboja which we can conclude that work culture  of there had good enough. Then the factor which influence towards apparatus’s work culture are related to inovation, the target, good environment work, and competition between the apparatus.